2000
DOI: 10.1209/epl/i2000-00473-7
|View full text |Cite
|
Sign up to set email alerts
|

The defect density waves in Zr 0.98 Sn 0.02 TiO 4 single crystal with incommensurately modulated structures: Neutron diffraction study

Abstract: We demonstrate the formation of defect-density waves in incommensurately modulated phases of Zr0.98Sn0.02TiO4 single crystal using neutron diffraction. A new state of the modulated structure can be explained in terms of a superposition of several modulation waves along a single crystallographic direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In ref. [1], Park claims to present for the first time direct structural evidence of defect density waves (DDW) by using Zn 0.98 Sn 0.02 TiO 4 and gives an interpretation of memory effects in incommensurate systems. In a publication [2] that predates [1] we have presented diffraction evidence for the formation of DDW and of a memory effect in incommensurately modulated structures for the first time using single-crystal thiourea (SC(NH 2 ) 2 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In ref. [1], Park claims to present for the first time direct structural evidence of defect density waves (DDW) by using Zn 0.98 Sn 0.02 TiO 4 and gives an interpretation of memory effects in incommensurate systems. In a publication [2] that predates [1] we have presented diffraction evidence for the formation of DDW and of a memory effect in incommensurately modulated structures for the first time using single-crystal thiourea (SC(NH 2 ) 2 ).…”
mentioning
confidence: 99%
“…[1], Park claims to present for the first time direct structural evidence of defect density waves (DDW) by using Zn 0.98 Sn 0.02 TiO 4 and gives an interpretation of memory effects in incommensurate systems. In a publication [2] that predates [1] we have presented diffraction evidence for the formation of DDW and of a memory effect in incommensurately modulated structures for the first time using single-crystal thiourea (SC(NH 2 ) 2 ). It was shown that additional satellites in the diffraction pattern form due to the superposition of coexisting waves and that the memory effect reflects an equality of the periods of the coexisting structural modulations near the temperature of thermal stabilization.…”
mentioning
confidence: 99%
See 2 more Smart Citations